Potassium supplying capacity of representative soils of South Western Nigeria as measured by intensity, quantity and capacity factors. - M. T., Adetunji; J. A., Adepetu (Universiti Putra Malaysia Press, 1993)
Laboratory and greenhouse studies were undertaken to determine the usefulness of K Quantity, Intensity and Capacity factors in evaluating K supply capacities and in predicting K uptake by maize in 14 representative soils of South Western Nigeria. The results showed that the activity ratio was a poor index of the available K and was incapable of correct prediction of K uptake during prolonged cropping. The potential Buffer Capacity was higher in the soils on basement complex than in soils derived from sedimentary origin, indicating that depletion of K on cropping will be faster in soils derived from sedimentary rocks than those on the basement complex. The results also showed that the 'fixed K' Quantity factor and the Potential Buffer Capacity could provide useful information in characterising the differential Buffer behaviour of soils.